PENDAMPINGAN PENINGKATAN KAPASITAS PRODUKSI DAN KUALITAS PENGEMASAN MELALUI HIBAH MESIN PRESS DESA DUWET, KABUPATEN MALANG - Alvin Nouval; Hilda Cahyani; Ellyn Eka Wahyu; Galuh Zuhria Kautzar; Cahyo Ramadhan Pratama (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to provide assistance to members of the Dasa Wisma group in Duwet Village, Tumpang District, Malang Regency. The many local beverage products produced by residents of this village face challenges in production capacity and packaging quality. The manual packaging process still in use often results in untidy packaging, low durability, and less appealing product appearance. This situation not only hinders broader product marketing but also reduces competitiveness in the market. To address these issues, the procurement of cup and packaging sealing machines is an effective solution. These machines can speed up the packaging process while improving the quality and appeal of local products. This community service activity involves the procurement of cup and packaging sealing machines and guidance on their use for producers in Duwet Village, Tumpang District, Malang Regency. The provision of these tools can offer significant benefits, such as increasing packaging efficiency; ensuring tidier, stronger, and more visually appealing packaging; supporting product protection during distribution; enhancing product competitiveness in wider markets; and ensuring consistent packaging quality on an ongoing basis. With this solution, residents of Duwet Village can be more competitive while also boosting the economic growth of the local community.